2021
DOI: 10.4314/ijbcs.v15i3.28
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of artisanal and small-scale gold mining on soils in northern regions of Côte d’Ivoire: cases of Boundiali, Korhogo and Tengrela

Abstract: The development artisanal and small-scale gold mining in recent years in Côte d'Ivoire could pose a risk to soils and health of local communities. This study aimed at assessing the impacts of artisanal and small-scale gold mining on the soils in the areas in the northen localities (Boundiali, Korhogo and Tengrela) of Côte d’Ivoire, where those activities are accentuated. Field observation and physico-chemical parameters analysis (potential hydrogen (pH), cation exchange capacity (CEC), organic matter (OM)) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The ferralitic soil retains Hg through adsorption although it lacks other nutrients. The Hg is associated with organic carbon, and later this complex compound is retained in ferralitic soil by Al/Fe oxyhydroxides [69]. Hg retention in tropical soils are controlled by the geochemical contents and texture.…”
Section: Mercury In Soil and Plant Lifementioning
confidence: 99%
“…The ferralitic soil retains Hg through adsorption although it lacks other nutrients. The Hg is associated with organic carbon, and later this complex compound is retained in ferralitic soil by Al/Fe oxyhydroxides [69]. Hg retention in tropical soils are controlled by the geochemical contents and texture.…”
Section: Mercury In Soil and Plant Lifementioning
confidence: 99%
“…However, in view of the illegal and clandestine nature of the artisanal mining activity, it completely escapes the control of the authorities in charge of environmental management. Thus, several studies have been carried out in particular in the West [10], in the Central West [3], in the North-East [2], and in the North-west [11] of the country, in order to examine artisanal gold mining practices, with a view to controlling their various environmental nuisances. All of these works have shown that artisanal gold mining has a detrimental effect on the soil, water resources, air, flora, fauna, the social environment, and the health of populations.…”
Section: Introductionmentioning
confidence: 99%